Development and characterization of a chicory extract fermented by Akkermansia muciniphila: An in vitro study on its potential to modulate obesity-related inflammation - A. Chervet; R. Nehme; C. Defois-Fraysse; C. Decombat; C. Blavignac; C. Auxenfans; B. Evrard; S. Michel; E. Filaire; J.-Y. Berthon; A. Dreux-Zigha; L. Delort; et al. (Current Research in Food Science)
Obesity, the fifth leading cause of death globally and linked to chronic low-grade inflammation and development of numerous severe pathologies, is a major public health problem. Fermented foods, probiotics, and postbiotics emerge as promising avenues for combating obesity and inflammation. The aim of our study was to develop and characterize phyto-postbiotics corresponding to prebiotic compounds fermented by gut bacteria, which could act on obesity and related-inflammation. Chicory extract fermented by Akkermansia muciniphila (C-Akm) was selected as the most antioxidant of 20 fermented extracts. The identification of metabolites derived from C-Akm extract has enabled us to detect mostly amino acids, acids, and some polyphenols (daidzein and genistein). The anti-inflammatory and anti-obesity activities of C-Akm extract were studied by testing the extract (50 μg/mL) on the polarization of THP-1 into macrophages, the secretion of pro-inflammatory cytokines in LPS-stimulated PBMCs, and the secretion of leptin and adiponectin in adipospheroids derived from human adipose stem cells. Finally, the extract was examined in 3D co-culture model mimicking inflamed obese adipose tissue. We found that C-Akm extract decreased ROS generation, TNF-α and Il-6 gene expression in polarized macrophages, INFγ and IL-17A secretion in LPS-stimulated PBMCs stimulated with LPS. It also decreased leptin expression while increasing adiponectin and HSL expression levels in both adipocytes and co-cultures. In addition, C-Akm extract stimulated adiponectin secretion in the co-culture model. Finally, our in vitro investigations demonstrated the potential benefits of C-Akm extract in the prevention and treatment of obesity-related inflammation.